PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAME TOURNAMENT (TGT) BERBANTUAN MEDIA MOLYMOD PADA MATERI HIDROKARBON KELAS X SMA NEGERI 4 SINGKAWANG - Pratiwi, Dewi; Muharini, Rini (Jurnal Pendidikan Matematika dan IPA, 2010)
The aim of this research is to know the effect of cooperative learning model, Teams Game Tournament (TGT) type, toward students achievement on hydrocarbon material, class X SMA Negeri 4 Singkawang. A quasi experimental method using pre-posttest control group design was implemented in this research. Data collecting tool used is essay test which has realibility of 0,59. Intact group random sampling technique was taken to get XA and XB classes as samples. Based on their daily chemistry examination, class XA was picked up as control class and XB was experiment class. U Mann Whitney test on students pretest showed no significantly difference between control and experiment class (Zhitung = -1,15, Ztabel = 1,96, ?=5%). Meanwhile, U Mann Whitney test on students posttest indicated significant difference between experiment and control class (Zhitung = -2,54, Ztabel = 1,96, ?=5%). The calculation of effect size resulted on posttest was 0,64 (23,89%). It showed that cooperative learning model TGT type gives intermediate level of effect size toward students achievement.Keywords: students achivements, cooperatif learning, Teams Game Tournament model, Hydrocarbons